Fibroblast growth factor‐21, body composition, and insulin resistance in pre‐pubertal and early pubertal males and females. (8th August 2014) - Hanks, Lynae J.; Casazza, Krista; Ashraf, Ambika P.; Wallace, Stephenie; Gutiérrez, Orlando M.
Summary Objective Accumulating evidence derived primarily from animal models suggests that fibroblast growth factor‐21 (FGF‐21) may affect the musculoskeletal system via effects on the capacity of tissues to respond to insulin. A proportion of musculoskeletal properties and underpinnings of promoting/preventing insulin resistance are established early in the pubertal transition. Thus, the objective of this study was to test the hypothesis that insulin resistance and/or obesity will promote greater FGF‐21 concentration which will be inversely associated with musculoskeletal parameters [lean mass and bone mineral content (BMC)] in pre‐/early pubertal children. Given the sexual dimorphic nature of musculoskeletal development of fat mass accrual, differences by obesity status and sex were also investigated. Design Cross‐sectional. Patients Children ages 7–12 years (n = 69, 38% male, 48% non‐Hispanic black, 45% obese). Measurements Fasting FGF‐21, glucose and insulin measures were obtained. An estimate of insulin resistance was derived using the homoeostatic model assessment of insulin resistance (HOMA‐IR). Body composition (BMC, lean mass and fat mass) was assessed by DXA. Multivariate regression analysis was used to evaluate the influence of FGF‐21 on BMC, lean mass and HOMA‐IR as dependent variables. Obesity status was established based on BMI z‐score. Results FGF‐21 concentrations did not differ by obesity status or by sex. There was an inverse association between FGF‐21 and BMC among nonobese individuals (P = 0·01) and an inverse association between FGF‐21 and lean mass among females (P = 0·02), which were both independent of fat mass. FGF‐21 was inversely associated with HOMA‐IR in males, but not females (P = 0·04). Conclusions The existence of relationships of FGF‐21 with musculoskeletal parameters and insulin resistance raises the possibility of crosstalk between these systems. These findings suggest that circulating FGF‐21 may differ in its association with bone, lean mass and insulin resistance depending on sex and weight status.